Study of satisfaction of extension workers on some administrative dimensions of agricultural extension organizations in Sharkia Governorate - Egypt - Omar, Ibrahim Abdel Wahab Mahmoud Mousa; Basha, Rania Hamdy Abdel Sadak (Arab Journal for Sciences and Research Publishing, 2016)
This study aimed at the relationship between satisfaction with the method of making administrative decisions and the method of promotion and keeping pace with the development of the extension service and studying the general and administrative characteristics of the agricultural extension instructors, and determining the relationship between the satisfaction of the method of making administrative decisions and the method of administrative promotion for the workers in agricultural extension and independent variables studied, The development of the extension service and the independent variables studied, determining the contribution of the independent variables combined in the interpretation of variance in the variables of each of them separately. Al-Sharqia Governorate. All the specialists in the Directorate and all the heads of agricultural extension departments in the agricultural departments and all the managers of the extension centers in the governorate were selected in a deliberate manner. The rest of the sample were randomly selected from the agricultural extension agents from 3 administrative centers: Zagazig, From January to May 2015, and the size of the sample was determined as the number of (100) respondents, and obtained the data for the research through questionnaires collected in the personal interview with the agricultural extension, and the use of the statistical data in the analysis B The most important results for the satisfaction of the method of administrative decision making and the method of administrative upgrading of agricultural extension workers were: (98%) of the respondents were between low and medium (2%) of them had high opinions, and there was a correlation between this variable and both (the educational qualification, the number of training courses and technical training, the practice of other work after the official working hours, forms of censorship and manifestations of corruption, d) JH management's attention to raise the experiences of agricultural extension agents, the general characteristics of the management, charging wages and incentives criteria).
Keywords: satisfaction; management and promotion style; extension service; job commitment; criteria for receiving wages and incentives; degree of management interest in raising the expertise of agricultural extension agents